Optimization of sales by applying e-commerce and digital marketing through social networks - Lazo-Amado, Misael; Meyluz, Paico-Campos (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Companies must have a strategy plan to satisfy their users and implement new methods to work with technology since people nowadays are more related to technology avoiding traditional sales and having virtual sales is why it has the objective of optimizing sales in companies by applying e-commerce and digital marketing through social networks. The methodology was carried out with Scrum, which has five stages (planning meeting, sprint backlog, daily meetings, sprint review, and retrospective review) that allows to comply with each established sprint showing as a result a functional project. As a result indicates the solution of each phase of the methodology getting the ecommerce system, with a validation by 7 experts specialized in (realism, integration, adaptability, technology, innovation, functionality, and usability) indicating a total of 93% showing a perfect state of the system and meets the satisfaction for the user and finally indicates the development of digital marketing by the social network Facebook showing a great improvement in their sales reaching up to triple their sales.